Dry cupping in the treatment of individuals with non-specific chronic low back pain: a protocol for a placebo-controlled, randomised, double-blind study - Bruno T Saragiotto; Hugo Jario de Almeida Silva; Caio Alano de Almeida Lins; Marcelo Cardoso de Souza; Rodrigo Scattone Silva (BMJ Open)
Background Low back pain is a very prevalent condition in the population and cupping therapy has been presented as a frequently used non-pharmacological treatment in this population. However, there is a lack of well-designed studies that evaluate the effects of this technique. This protocol describes a placebo-controlled, randomised, double-blind study that aims to evaluate the effect of dry cupping therapy on pain, physical function, trunk range of motion, quality of life and psychological symptoms in individuals with non-specific chronic low back pain.Methods and analysis Ninety individuals with chronic non-specific low back pain, aged from 18 to 59 years, will be randomised into two groups: intervention group, which will be submitted to dry cupping therapy application with two suctions; and placebo group which will undergo placebo dry cupping therapy. Both applications will occur bilaterally in parallel to the vertebrae from L1 to L5. The application will be performed once a week for 8 weeks. The volunteers will be evaluated before the treatment (T0), immediately after the first intervention (T1), after 4 weeks of intervention (T4) and after 8 weeks of intervention (T8). The primary outcome will be pain intensity, and secondary outcomes will be physical function, lumbar range of motion, patient expectation, overall perception of effect, quality of life and psychological factors.Ethics and dissemination This protocol has been approved by the Ethics Committee of FACISA/UFRN (number: 3639814). The results of the study will be disseminated to participants through social networks and will be submitted to a peer-reviewed journal and scientific meetings.Trial registration number NCT03909672.